The Functioning of Ukraine’s Budgetary System in Wartime Conditions - Sokrovolska, Nataliia; Kucher, Galyna; Pyvovarov, Kostyantyn; Mazur, Hennadii; Poliak-Sverhun, Mariana (International Journal of Economics and Financial Issues, 2025)
The proper functioning of a budgetary system during wartime is crucial for supporting a country’s defense capabilities and fulfilling its essential social functions. This study aims to analyze key indicators of the efficiency and security of Ukraine’s budgetary system in wartime conditions. The research employed methods such as economic and statistical analysis, comparative analysis, and normative and marginal analysis. The results of the study analyzed trends in state budget expenditures and revenues. A separate analysis of the budget deficit showed a significant increase (to more than 20% in 2023), indicating a need for additional financing. The structure of state budget revenues and expenditures has also changed significantly. The share of tax revenues has decreased, while defense spending constitutes about 50% of expenditures. However, the main problem remains the growing external state debt, which has nearly reached 100% of GDP. At the same time, the available gold and foreign exchange reserves can cover only 40% of the debt. Based on the research conducted, recommendations were formulated that can guide government officials in shaping future budgetary and tax policy.